Analisis Efektivitas Penyampaian Bahasa Dalam Buku How To Win And Influence People - Ghazi Alghifari Maulidan Ryanto; Firdaus Ramadhani Triandi; Farras Syakira Ardiyanti; Hana Dwi Ramadhani; Natalia Desy Anggraeni (CV. ITTC INDONESIA, 2024)
The book “How to Win Friends and Influence People” by Dale Carnegie is a book that discusses how to build relationships between people using effective communication methods. Effective communication is useful for attracting the attention of others, maintaining a relationship, and building a good self-image. This research aims to enable readers to understand the content of the material conveyed by Dale Carnegie through the book “How to Win Friends and Influence People” about the application of good and effective communication principles and strategies in everyday life. This research uses a descriptive qualitative method of literacy based on literature study with books, e-books, and scientific articles as references. This research method prioritizes the analysis of what has been read and concludes it with academic language. The overall content in this book includes basic techniques in handling people, how to make yourself liked by people, how to attract people with your mindset, and how to become a good leader.